Profiling Participants Of The Rainforest World Music Festival - Ahmad, Shuib; Salbiah, Edman; Norjumawati, Sabran (Education and Novel Technology Research Association, 2013)
For tourism marketers and event organizers, the identification and understanding of the customers are important for market segmentation. Profiling the tourists allows segmentation to be done on the basis of the person who makes the trip. The main objective of the study is to identify the characteristics of the participants of the annual music festival in Santubong, Sarawak. The satisfaction of the participants on the services provided and the facilities available is evaluated using the perception analysis on the services and facilities. On-site data are collected from a sample of the visitors to the three days festival; the data include all associated expenditures spent in the area during the festival. The results of the study show that 34%, 18% and 48 % of the visitors participate in 1, 2 and 3 days in the festival, respectively. The average total expenditure per participant per day is about RM477 giving an estimated gross total expenditure during the 2009 festival of about RM9.62mil. Of the international visitors, 57% are from Europe, 33% from Australia and New Zealand, 4% from America, 5.9% from other Asian countries. The majority of the participants prefer to stay in hotels in the city than in hotels near the site of the festival because they could find more tourism products and services in the city. Most participants are satisfied with the services and facilities available at the festival site; however, the main concerns of some of the participants are the cleanliness of the toilets, the availability of transportation, and the parking facilities. The organizers and marketing agencies involved could use information from profiling studies to plan strategies to increase participation of music enthusiasts as well as non enthusiasts in the future.